Cationic polyelectrolytes as convenient electron extraction layers in perovskite solar cells. (November 2020) - Kang, Ju Hwan; Park, Yu Jung; Khan, Yeasin; Ahn, Yohan; Seo, Jung Hwa; Walker, Bright
Abstract: The potential of hybrid organic-inorganic perovskite solar cells (PSCs) as a next-generation photovoltaic technology has attracted enormous research interest due to their remarkably low cost and outstanding photo-physical properties. Increasing their power conversion efficiency (PCE) using materials which are similarly low-cost as the perovskite layer remains a critical issue for their commercialization; interlayers play important roles in elevating the PCEs of PSCs and the commonly used interlayers used in PSCs are typically orders of magnitude more costly than the perovskite layer itself. Herein, we report the effect of polyelectrolytes on the energy band structure and device characteristics when they are incorporated as electron extraction layers (EELs) of photovoltaics with both N–I–P and P–I–N geometries. To tune and improve device performance, we used cationic nonconjugated polyelectrolytes (NPEs) based on the poly(ethyleneimine) (PEI) backbone with different anions including bromide (Br − ), iodide (I − ), and tetrakis (imidazole) borate (BIm4 - ). This series of NPEs formed electric dipoles at the NPE/metal electrode interfaces; consequently allowing tuning of the energy levels, and work functions (WFs) of the electrodes. Notably, the PCE could be improved from 8.11 to 14.71% in the case of the NIP geometry, or from 7.40 to 13.79% in the case of the P–I–N geometry using a PEIH + BIm4 − interlayer. Ultraviolet photoelectron spectroscope (UPS) results reveal that all of the polyelectrolytes, and particularly PEIH + BIm4 − effectively decreased the WFs of the metal electrodes. Interestingly, a tunable dipole was achieved on the conducting surfaces (e.g. both cathode and anode electrodes) modified with electrolytes by simply varying the identity of counterions, as verified by the significantly reduced effective WF. These n-Type electrolytes created Ohmic contacts between the electrodes and the perovskite layer. These findings demonstrate that NPEs are effective EELs for high efficiency PSCs. Graphical abstract: Image 1 Highlights: Nonconjugated electrolytes (NPEs) with different counterions for electron extraction materials were demonstrated. The performance of the perovskite solar cells was dependent on the size of the counterion. Tunable dipoles were achieved on the ITO substrates by varying the size and identity of the counterions. The relationship between the counterion size of NPEs and the device performance was proposed.